2006
DOI: 10.1096/fj.05-5639fje
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein CI stimulates the response to lipopolysaccharide and reduces mortality in Gram‐negative sepsis

Abstract: Gram-negative sepsis is a major death cause in intensive care units. Accumulating evidence indicates the protective role of plasma lipoproteins such as high-density lipoprotein (HDL) in sepsis. It has recently been shown that septic HDL is almost depleted from apolipoprotein CI (apoCI), suggesting that apoCI may be a protective factor in sepsis. Sequence analysis revealed that apoCI possesses a highly conserved consensus KVKEKLK binding motif for lipopolysaccharide (LPS), an outer-membrane component of gram-ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 59 publications
5
71
1
Order By: Relevance
“…In cases where Grs potentiate pathways induced by TLR ligands independent of the Gr catalytic activity (48), the focus should lie on clarifying how Grs modulate these pathways via interaction with signaling molecules. A common characteristic in LPS-enhancing proteins such as LPS-binding protein (71,72), Grs (48), the neutrophil granule protein azurocidin (73,74), high mobility group box-1 protein (75,76), protamines (77), and apolipoprotein C1 (78,79) is the presence of cationic patches of arginines and/or lysines that drive the interaction with LPS. Endocytosis may also play a role, because internalization is required for the stimulating effect of azurocidin on LPS-induced cytokine responses (80).…”
Section: Unresolved Questionsmentioning
confidence: 99%
“…In cases where Grs potentiate pathways induced by TLR ligands independent of the Gr catalytic activity (48), the focus should lie on clarifying how Grs modulate these pathways via interaction with signaling molecules. A common characteristic in LPS-enhancing proteins such as LPS-binding protein (71,72), Grs (48), the neutrophil granule protein azurocidin (73,74), high mobility group box-1 protein (75,76), protamines (77), and apolipoprotein C1 (78,79) is the presence of cationic patches of arginines and/or lysines that drive the interaction with LPS. Endocytosis may also play a role, because internalization is required for the stimulating effect of azurocidin on LPS-induced cytokine responses (80).…”
Section: Unresolved Questionsmentioning
confidence: 99%
“…Septic HDLs are almost depleted of apoC-I (Barlage et al 2001). ApoC-I contains a consensus LPS-binding motif and is able to enhance the biological response to LPS thus reducing mortality in mice with Gram-negative-induced sepsis (Berbee et al 2006). In fact, apoC-I binds to LPS and prevents its clearance by the liver and spleen, resulting in the stimulation of the LPS-induced pro-inflammatory response and protection against septic death (Berbee et al 2006).…”
Section: Interaction Of Hdl With Lps and Gram-negative Bacteriamentioning
confidence: 99%
“…ApoC-I contains a consensus LPS-binding motif and is able to enhance the biological response to LPS thus reducing mortality in mice with Gram-negative-induced sepsis (Berbee et al 2006). In fact, apoC-I binds to LPS and prevents its clearance by the liver and spleen, resulting in the stimulation of the LPS-induced pro-inflammatory response and protection against septic death (Berbee et al 2006). These findings suggest that when LPS is released into the plasma following bacteria proliferation in the blood, apoC-I binds to LPS and presents it to responsive cells such as macrophages, leading to a rapid and enhanced production of pro-inflammatory cytokines, which are essential for effective eradication of the bacterial infection.…”
Section: Interaction Of Hdl With Lps and Gram-negative Bacteriamentioning
confidence: 99%
“…In fact, we have demonstrated that replacement of the Lys residues within this motif by Ala residues (i.e., AVAEALA ), which neutralizes positive charges without changing the protein structure, decreased the binding to LPS and partly reduced the ability of apoCI to stimulate the LPS-induced TNF ␣ response ( 19 ). However, in addition to the KVKEKLK motif, apoCI contains a number of alternating cationic/hydrophobic motifs throughout its structure.…”
mentioning
confidence: 99%